Evidence an Alex Delaware novel - Kellerman, Jonathan (Ballantine Books, 2009)
Veteran homicide cop Milo Sturgis and psychologist Alex Delaware expose the shadowy side of glittering Los Angeles as they investigate the gruesome death of a young couple-murdered in flagrante--the man identified as a notorious womanizer and eco-friendly architect, the woman unidentified--in this unforgettable tale spiced with eco-terrorism, arson, blackmail, conspiracy, and a vendetta that runs deep.